Alcoholics Anonymous-Related Benefit for Urban Native Americans: Does Urban Native American Gender Moderate AA Engagement and Outcomes?. Issue 1 (2nd January 2017) - Muñoz, Rosa E.; Tonigan, J. Scott
ABSTRACT: Alcoholics Anonymous (AA) is one of the most commonly accessed resources for individuals seeking to reduce their drinking. How urban Native Americans fare in AA is only beginning to be investigated in spite of circumstantial evidence suggesting that a majority of treatment-seeking urban Native Americans will receive 12-Step treatment. Even less is known about Native American gender differences with regard to AA-related benefit. The current study addressed this gap by investigating urban Native American gender differences in AA attendance rates and outcomes. To this end, as part of two larger National Institutes of Health-funded studies we recruited 63 Native American men and women and followed them for 9 months in this naturalistic study ( n = 35 males, n = 28 females). Urban Native Americans significantly reduced their drinking over the study period, and AA attendance explained, in part, increased abstinence of study participants. No significant differences in AA attendance and drinking outcomes were observed between Native American men and women; however, descriptively men reported greater reductions in hazardous drinking relative to women. Clinical implications and future directions are discussed.